If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2y+3=-11
We move all terms to the left:
-2y+3-(-11)=0
We add all the numbers together, and all the variables
-2y+14=0
We move all terms containing y to the left, all other terms to the right
-2y=-14
y=-14/-2
y=+7
| 1-5a+5=-6-2a | | 7z+2z+z=10 | | -76=4(3b-1) | | 6t+4t-6t+2t+t=14 | | (5x+6)+64=180 | | 59+3x=90 | | 9x-7x-x+4x=15 | | 1/8b=64 | | 10=q/6 | | -84=-4(1-4x) | | 11n-n-6n=20 | | -84=-4(1-4x | | 13+2x-9=5x-4-(-3x) | | 8x+4x-14=22 | | 3x−2=18+x | | 1+x-5x=9 | | 6n–5=19 | | 29(x+9)=24 | | −6=−8+p/11 | | 6(3p-2)=-120 | | 2(2w+5)-6w=-3w+18-3w+24 | | 7x-13=5x+4 | | 7y+10=31 | | 11=8(m-3)+4m-1 | | x–6/2=4x/7 | | -70=-2(5v+5) | | -3x-1-5x=-9 | | 5=z−251 | | 3(5g+2)/2=63 | | 3y-9=54 | | 98=s+24 | | -70=-2(5v+5 |